Design Optimal Premium for Financially Balanced Bonus Malus System - MUBAROK (NIM 20806003), AOH
BMS that financially balanced can be seen from the average premium income paid by the policyholders to the company each years. These average premiums is constant, this is because maluses paid by bad drivers cover the company expense for paying bonuses to good drivers. In this thesis we will discuss how to design an optimal premium tariff structure as such the BMS is financially balanced using transition rules. The optimal premium is calculated by minimizing a quadratic function of the difference between the premium for an optimal BMS with an infinite number of classes and the premium for a BMS with a finite number of class, weighted by the stationary probability of being in a certain class, and by imposing various constraints on the system.